ABSTRACT IMPLEMENTATION OF A KIND TO MANAGE DATA SETS USING PROGRAMMING LANGUAGE C + + - Ruiz L., Edgar (2003)
This article presents the implementation of a data abstract type to represent the Set Theory Mathematical Concept, The program has been written in C++ Program Language applying the Object Oriented Programming Paradigm through a Dev C++ v.4.1 Compiler, a GNU compiler with GPL licence.